Hybridization rate and climate change: Are endangered species at risk? - Sánchez-Guillén, Rosa (2014)
Many species are altering their geographic range due to climate change creating new sympatric populations of otherwise allopatric populations. We investigated whether climate change will affect the distribution and thus the pattern of hybridization between two pairs of closely related damselfly species [Ischnura damula and I. demorsa, and I. denticollis and I. gemina (this, an endangered species)]. Thus, we estimated the strength of pre and postmating reproductive barriers between both pairs of species, and we predicted future potential distribution under four different Global Circulation Models and a realistic emissions scenario of climate change by using maximum entropy modelling technique. Our results showed that reproductive isolation (RI) is complete in I. damula × I. demorsa individuals: F1 (first generation) hybrids are produced but do not reach sexual maturation. However, RI in I. denticollis × I. gemina hybrids is high but incomplete and unidirectional: only I. gemina females produced F1 hybrids which mate with males and females of I. denticollis and between them producing BC1 (backcrosses) and F2 (second generation) viable hybrids. Maximum entropy models revealed a northern and westward shift and a general reduction of the potential geographic ranges. Based on the pattern of hybridization, for I. damula and I. demorsa there is a current threat as well as a rapid displacement and/or extinction of I. gemina by I. denticollis. However, the current pattern of extinction may not continue due to the contraction in ranges of the four species. © 2014 Springer International Publishing Switzerland.